A nonlinear optical switch induced by an external electric field: inorganic alkaline–earth alkalide. Issue 29 (29th May 2019) - Li, Bo; Peng, Daoling; Gu, Feng Long; Zhu, Chaoyuan
Abstract : The inorganic alkaline–earth alkalide M(NH3 )6 Na2 (M = Mg or Ca) can serve as a potential candidate for a nonlinear optical switch. Abstract : Exploring a new type of nonlinear optical switch molecule with excess electron character is extremely important for promoting the application of excess electron compounds in the nonlinear optical (NLO) field. Here, we report external electric field (EEF) induced second-order NLO switch molecules of inorganic alkaline–earth alkalides, M(NH3 )6 Na2 (M = Mg or Ca). The centrosymmetric structure of M(NH3 )6 Na2 is destroyed in the presence of an EEF, and then a long-range charge transfer process occurs. It has been found that excess electrons are gradually transferred from one Na atom to the other Na atom through the inorganic metal cluster M(NH3 )6 . Finally, the excess electrons are completely located on one of the two Na atoms. In particular, the electronic contribution of the static first hyperpolarizability ( β e0) for M(NH3 )6 Na2 exhibits a large significant difference when the EEF is switched on. The β e0 value of M(NH3 )6 Na2 is 0 when EEF = 0, while the peak β e0 values are 5.95 × 10 6 (a.u.) for Mg(NH3 )6 Na2 (EEF = 58 × 10 −4 (a.u.)) and 1.83 × 10 7 (a.u.) for Ca(NH3 )6 Na2 (EEF = 53 × 10 −4 (a.u.)). This work demonstrates that the compounds M(NH3 )6 Na2 can serve as potential candidates for NLO switches.